2018
DOI: 10.1038/s41398-017-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate enhances mitochondrial function during oxidative stress in cell lines from boys with autism

Abstract: Butyrate (BT) is a ubiquitous short-chain fatty acid (SCFA) principally derived from the enteric microbiome. BT positively modulates mitochondrial function, including enhancing oxidative phosphorylation and beta-oxidation and has been proposed as a neuroprotectant. BT and other SCFAs have also been associated with autism spectrum disorders (ASD), a condition associated with mitochondrial dysfunction. We have developed a lymphoblastoid cell line (LCL) model of ASD, with a subset of LCLs demonstrating mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 109 publications
8
131
0
Order By: Relevance
“…In our study, evaluation of mitochondrial bioenergetics activity using a metabolic flux analyzer showed that ASD fibroblasts presented altered parameters of mitochondrial respiration including higher maximal respiratory capacity, reserve capacity, and proton‐leak respiration. These data are in agreement with other recent studies in which Rose and colleagues demonstrated that immortalized lymphoblastoid cells derived from children with ASD present significant abnormalities in mitochondrial respiration at baseline, with these abnormalities worsening following exposure to different pro‐oxidant stimuli 22‐25 . Indeed, similarly to our results, when examined in basal condition, ASD lymphoblastoid cells exhibited abnormally high maximal respiratory capacity, reserve capacity, and proton‐leak respiration coupled with higher glycolysis and glycolytic reserve 22‐25 .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, evaluation of mitochondrial bioenergetics activity using a metabolic flux analyzer showed that ASD fibroblasts presented altered parameters of mitochondrial respiration including higher maximal respiratory capacity, reserve capacity, and proton‐leak respiration. These data are in agreement with other recent studies in which Rose and colleagues demonstrated that immortalized lymphoblastoid cells derived from children with ASD present significant abnormalities in mitochondrial respiration at baseline, with these abnormalities worsening following exposure to different pro‐oxidant stimuli 22‐25 . Indeed, similarly to our results, when examined in basal condition, ASD lymphoblastoid cells exhibited abnormally high maximal respiratory capacity, reserve capacity, and proton‐leak respiration coupled with higher glycolysis and glycolytic reserve 22‐25 .…”
Section: Discussionsupporting
confidence: 93%
“…Butyrate increases the expression of the mitochondrial master regulator, PGC1‐α α, to induce mitochondrial biogenesis and oxidative metabolism in cells and in skeletal muscle of C57BL/6 mice . Furthermore, butyrate induced the expression of genes involved in both mitochondrial fission ( Drp‐1 , Fis‐1 ) and mitophagy ( Pink‐1 , Lc3 , Pten), in vitro , suggesting that SCFAs produced primarily from gut microbiome can fine‐tune mitochondrial function, biogenesis, and dynamics .…”
Section: Introductionmentioning
confidence: 97%
“…76 The intestinal microbiota is also known to produce SCFAs, which include acetate, butyrate, and propionate from dietary fiber. 81 The important role of butyrate in mitochondrial functionality has been demonstrated in colonocytes. Moreover, acetate and butyrate have been demonstrated to systemically circulate to the brain, increasing brain mitochondrial function.…”
Section: Intestinal Microbiota On Mitochondriamentioning
confidence: 99%